ATTRIBUTE-BASED EVALUATION OF DENGUE SURVEILLANCE IN SUMENEP REGENCY: ASSESSING EFFECTIVENESS AND RECOMMENDATIONS FOR IMPROVEMENT: Evaluasi Surveilans Demam Berdarah Dengue Berbasis Atribut di Kabupaten Sumenep: Menilai Efektivitas dan Rekomendasi Perbaikan - Yuliani, Cahya; Hidajah, Atik Choirul; Susilastuti, Fransisca; Suryadinata, Mohammad Agus; Soares, Virgilio (Jurnal Berkala Epidemiologi, 2025)
Background: Dengue Hemorrhagic Fever remains a significant public health concern in Sumenep Regency, with cases and fatalities reported annually. In 2023, both the incidence rate (27.74/100,000 population) and the case fatality rate (1.96%) exceeded the national targets (IR ≤10; CFR ≤0.6%). Therefore, evaluating the dengue surveillance system is essential to assess its performance and support effective control measures. Purpose: This study evaluates the dengue surveillance system in Sumenep Regency in 2023 based on surveillance system attributes to provide recommendations for improvement. Methods: The study was conducted at a public health center (puskesmas) and the Regency Health Office, involving 17 informants, including surveillance officers and DHF program managers. Data were collected through interviews, document reviews, and observations using questionnaires and sheets. Analysis was based on surveillance system attributes aligned with Indonesia’s DHF prevention and control guidelines, with results presented in tables and narratives. Results: The surveillance system demonstrated good data stability and timeliness, but remains complex, inflexible, has low user acceptance, is not yet representative, and is not yet sensitive. Conclusion: The dengue surveillance system in Sumenep needs improvements in simplicity, user acceptance, representativeness, sensitivity, and data quality. Efforts should simplify processes, integrate active and passive surveillance, standardize procedures, and strengthen coordination to improve system effectiveness.